Odpowiedzi

2010-04-15T17:06:56+02:00
(4√3+2)*(√3-1)= 4√3 * √3 + 4√3 * (-1) + 2√3 -2 = 4*3- 4√3 +2√3 -2=
12 - 2√3 -2 = 10- 2√3 = 2(5-√3)

(√7-√3)(√7+√3)=√7*√7 + √7*√3 - √3*√7 - √3*√3 = 7 - 3 = 4

(1+3√2)² = 1²+2*1*3√2 +(3√2)²= 1+ 6√2 + 9*2=1+6√2 + 18 =19+6√2

(3-2√6)²=3² - 2* 3 *2√6 +(2√6)²= 9 -14√6+4*6= 3-12√6 = 3(1-4√6 )


jesli natomiast przed nawiasami były minusy a nie myślniki wyniki sa następujące:

-(4√3+2)*(√3-1)=(4√3+2)(1-√3)= 4√3-4√3*√3+2-2√3 =4√3-4*3+2-2√3=
2√3-12+2=2√3-10=2(√3-5)

-(√7-√3)(√7+√3)=(√3-√7)(√7+√3)= √21+√9-√49-√21=√9-√49=3-7=-4

-(1+3√2)² = -[1²+2*1*3√2 +(3√2)²]= -[1+ 6√2 + 9*2]=-[1+6√2 + 18] =-[19+6√2]=-19-6√2

-(3-2√6)²=-[3² - 2* 3 *2√6 +(2√6)²]= -[9 -14√6+4*6]= -[3-12√6] = 12√6-3 = 3(4√6-1)